2010
DOI: 10.1103/physrevlett.104.192501
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Nuclear Shell Gaps Studied in thed(Ne24,pγ)Ne25Reaction

Abstract: The transfer of neutrons onto 24 Ne has been measured using a reaccelerated radioactive beam of 24 Ne to study the ðd; pÞ reaction in inverse kinematics. The unusual raising of the first 3=2 þ level in 25 Ne and its significance in terms of the migration of the neutron magic number from N ¼ 20 to N ¼ 16 is put on a firm footing by confirmation of this state's identity. The raised 3=2 þ level is observed simultaneously with the intruder negative parity 7=2 À and 3=2 À levels, providing evidence for the reductio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 25 publications
3
48
0
Order By: Relevance
“…In addition to 31 Ne, there is now a body of experimental data on the very neutron-rich Ne isotopes [12,[17][18][19][20][21][22][23]. The structures of these isotopes evolve considerably as one moves toward the neutron drip line and are complex.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to 31 Ne, there is now a body of experimental data on the very neutron-rich Ne isotopes [12,[17][18][19][20][21][22][23]. The structures of these isotopes evolve considerably as one moves toward the neutron drip line and are complex.…”
Section: Introductionmentioning
confidence: 99%
“…3(b). In the low-lying positive-parity states, similar to 26 [41,42,[47][48][49][50]. The observed and calculated spectroscopic factors for those negative-parity states are large, and hence, their excitation energies are good measures for the p 3/2 and f 7/2 single-particle energies.…”
Section: B Low-lying Energy Spectra Obtained By β Gcmmentioning
confidence: 81%
“…Previous experiments have used a spectrometer at zero degress [1,8], but in this instance, a different solution was needed. An in-beam zero-degree detector, the TRIFOIL, was mounted at a distance of 40 cm downstream of the target.…”
Section: Trifoilmentioning
confidence: 99%
“…Experimental studies of 24 Ne [1] and 27 Ne [2] using the TIARA array have shown the reduction of the N=20 shell gap in favour of N=16. Deep inelastic studies have also been motivated, including one using a radioactive 24 Ne beam [3,4], where the 26 Na nucleus was populated but no spectroscopic results were published.…”
Section: Introductionmentioning
confidence: 99%